A Critical and Annotated Edition of Lope de Vega's Las almenas de Toro - Vega, Lope de, 1562-1635 (Studies in the Romance languages and literatures, 2019)
The only play of Lope de Vega's involving the Cid and Sancho II, this work has long been admired by critics of the Golden Age drama for its vitality and poetic character. This edition brings to light new variants and passages missing in the known printed editions.